Self-powered perovskite CH3NH3PbBr3 field effect transistor with fast response and high sensitivity in sensing - Hua Peng (Elsevier, 2021)
Organic-inorganic hybrid perovskite materials possess advantages over other candidate classes for chemo-sensory materials because of their structural tunability and stability. In this work, we prepared highly qualitied MAPbBr3 perovskite crystals to provide a high carrier mobility to enhance the sensing on gas, where the response time of sensing below 0.1 s is obtained. Because the perovskite field effect transistor provides a large surface to adsorb gas, the sensitivity of detection can reach 0.2 ppm. Furthermore, combining with theoretical simulation, we analyzed the binding energy, electronic structure, and charge transfer density between perovskite surface (including PbBr2-terminated surface and CH3NH3Br-terminated surface) and gas molecules to study the mechanism behind the phenomena. It is obtained that enhancing the interfacial charge transfer density and then suppressing the recombination of transferred charges will effectively increase the sensitivity of the sensor.